ASME 2019 2nd International Offshore Wind Technical Conference 2019
DOI: 10.1115/iowtc2019-7580
|View full text |Cite
|
Sign up to set email alerts
|

Concept Design and Analysis of Wind-Tracing Floating Offshore Wind Turbines

Abstract: Most of the existing floating offshore wind turbines (FOWT), whether in concept or built, host a single turbine. Structures that can host multiple turbines have received attention in recent years, mainly with the aim of reducing the overall cost of energy production and maintenance. A concept challenge of placing multiple wind turbines on a single floating platform is that under variable wind directions, the leading turbines may block the wind against the trailing turbines. In this work, concept design of a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The floater is triangular, supporting three wind turbines. A preliminary hydroelastic analysis of the wind-tracing floater is given in Lamei et al (2019) and concept design of the structure is discussed in Li et al (2019). Similarly, WindSea (Carbon Trust 2015) is a wind-tracing concept where the mooring lines are connected by a turret bearing to allow the platform to rotate and face the incoming wind, see Fig.…”
Section: Multi-unit Floater Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The floater is triangular, supporting three wind turbines. A preliminary hydroelastic analysis of the wind-tracing floater is given in Lamei et al (2019) and concept design of the structure is discussed in Li et al (2019). Similarly, WindSea (Carbon Trust 2015) is a wind-tracing concept where the mooring lines are connected by a turret bearing to allow the platform to rotate and face the incoming wind, see Fig.…”
Section: Multi-unit Floater Conceptmentioning
confidence: 99%
“…6 (for water depth h = −200 m and wave height H = 1 m). For co-directional wind flow to the towers, the total aerodynamic loading on the three rotors (standard 5 MW NREL turbine) reaches up to 3 MN at rated wind speed of U W = 11.4 m/s, see Lamei et al (2019) and Li et al (2019) for more details about this structure and the calculation.…”
Section: Hydrodynamic Loadsmentioning
confidence: 99%
“…Furthermore, the wind-tracing FOWT was introduced by Wong (2015) with three wind turbines and a weathervaning mechanism by turret-bearing mooring system. Preliminary analysis on its wave-induced responses and its motions to the combined wind and wave loads were reported by Lamei et al (2019) and Li et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The type of floating platform is selected based on the mooring system, the number of wind turbines, site requirements, construction, grid connection, and operating conditions of the sea [13]. Recently, the concept of multiple wind turbines on a floating platform has drawn attention because they are more stable and enable the use of higher towers and hence greater capture of wind energy [14][15][16][17][18][19][20][21][22][23]. The installation and mooring costs can be reduced by employing multiple wind turbines on a single platform as they can share common mooring lines [24].…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [20] showed that the heave plates with a minimal increase of mass can reduce the pitch and heave motions of a multi-unit offshore floating wind turbine. The concept of a triangular-shaped floating platform with three wind turbines at each corner was presented in [21,22] that considered only hydrodynamic loads to study the motion and elastic responses of the structure. This concept used a wind-tracing floating structure with a single-point mooring system that allows for the entire platform to rotate in response to the change of the wind direction.…”
Section: Introductionmentioning
confidence: 99%